A novel antiviral candidate from Moringa oleifera through dual targeting mechanism of SARS-CoV-2 protease: Computational Sscreening - Listiyani, Priscilla; Dhea Kharisma, Viol (Generasi Biologi Indonesia, 2023)
COVID-19 is triggered by SARS-CoV-2 which is related in a similar way to SARS-CoV and MERS-CoV. RdRp is an essential component of the virus in replication and transcription. RdRp triggers polymerase activity through binding to cofactors such as nsp7 and nsp8. Mpro plays an important role in viral protease activity for the assembly process. RdRp and Mpro can be used as targets to inhibit the replicative activity of SARS-CoV-2. Moringa oleifera is used by people around the world as a traditional medicine because it has antioxidant, anti-inflammatory, and antiviral properties. This study reveals the molecular mechanism of Moringa oleifera as an inhibitor of key proteins in SARS-CoV-2 replication through a computational approach. Additionally, the in silico method in this study consists of sample preparation in the database, druglikeness prediction, antiviral probability, virtual screening, chemical bond interaction, and 3D visualization. Moringa oleifera may have potential as an antiviral candidate through Ellagic Acid activity as a dual inhibitor through inhibition of SARS-CoV-2 replication and assembly. The candidate compound can generate weak bonding interactions such as hydrogen and hydrophobic to trigger binding stability at specific domains.